Exploring teaching strategies to improve the performance of grade 9 learners in mathematics in Mkhuhlu Circuit, Bohlabela District - Mthethwa, Venetia Sebenzile (My University, 2021)
This study explored the different teaching strategies which teachers use to teach mathematics in order to improve the performance of Grade 9 learners in the subject in Mkhuhlu Circuit; Bohlabela District of Education in Mpumalanga Province. The inability of Grade 9 learners to achieve the set minimum performance standard of a pass at level 3 (40%) in mathematics poses a challenge because mathematics is set as a pass requirement in the said grade and it is compulsory for all learners to enrol for this subject. The poor performance of learners in mathematics is attributed to inappropriate teaching strategies that teachers use in the teaching of this subject. There are lessons to be drawn from the practices of leading countries in learner performance in mathematics and this study sought to find alternative strategies that are appropriate for teaching Grade 9 learners and to improve their performance in mathematics in the circuit. The study used constructivism as its lens to look at the realities about learner performance in mathematics. Constructivism as a theory presents and unpacks the manner in which people learn and acquire knowledge. The participants for this study were sampled using a purposive sampling technique and samples were drawn from two secondary schools representing good and poor performance of Grade 9 learners in mathematics. Seven participants were engaged in this study and this sample included a principal, SMT member, and mathematics teacher from each school. A subject advisor for mathematics in the GET was also interviewed. This study adopted and followed a qualitative design of inquiry which included interviews, observation, and the analysis of documents and artefacts to collect data from the different respondents that were identified for this study. The inquiry was guided by the following research questions: Which teaching strategies do teachers normally use to teach mathematics in Grade 9 at Mkhuhlu circuit? There are two sub-questions which were used to support the main research question and they are: To what extent do teachers vary the strategies of teaching and which strategies and LTSM do the teachers use to teach mathematics in Grade 9? What is the level of support that teachers receive from the different levels of the system? Data was analysed by organizing the data collected using codes to summarize it and then interpret the coded data to identify themes, patterns and relationships. This study revealed that different teaching strategies have an impact on the learners’ academic performance in mathematics. It also emerged from this study that quality and effective teaching and learning of mathematics are grounded on the constructivist theory. This study also established that the choice and use of appropriate teaching strategies coupled with the availability of relevant resources contribute towards positive learning gains. Similarly, learners’ preferences of teaching and learning strategies must be considered towards the development and sustenance of a positive attitude towards mathematics. The study recommended that the Annual Teaching Plans should suggest teaching strategies to be used for a particular topic; and that teachers must specify their teaching strategies and their choice of resources in the planning of every lesson. The provision of resources, particularly for mathematics teaching must be made an apex priority. Subject advisors must give attention to the teaching strategies that teachers use in curriculum delivery and not only on content mastery and coverage. School Management Teams must follow-up on the implementation of ICT in their curriculum management and monitoring. The study further recommended that an analysis of results must shift from concentrating on the pass percentages and focus on the quality of the passes. The identified limitations of this study were methodological limitations and sample characteristic limitations where the size of the research sample was relatively small.
Thesis (M. Ed. (Curriculum Studies)) -- University of Limpopo, 2021
Keywords: Different teaching strategies; Teachers; Mathematics; Improve performance; Grade 9 learners; Mathematics -- Study and teaching; Teaching; Achievement motivation; Academic achievement -- South Africa -- Mpumalanga